Three Characterisctics of Atopy to Diagnose Allergy in Children with Respiratory Symptomps - Far-Far, Imanuel; Endaryanto, Anang; Setyoningrum, Retno Asih; Soegiarto, Gatot (Jurnal Kedokteran Brawijaya, 2020)
The prevalence of allergic diseases has increased in the last decade. Therefore, precise and reliable in predicting allergy in children were needed. However, in daily practice, most misdiagnosis occurs because it is only based on a family history of allergy. This study aims to evaluate the chronicity, recurrence of symptoms with similar exposure, and family history of allergy to be used as a predictor of allergy in children with respiratory symptoms. Cross sectional study was conducted in children who referred to the Pediatric Allergy and Immunology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya from January 1st - July 31st 2019. Children with a suspected allergy who developed respiratory symptoms was included. The data was taken from standardized medical record. The sensitivity and specificity of the 3 characteristics of atopic with positive SPT were calculated. A total of 115 children were admitted and 109 children fulfill the inclusion criteria. Gender 60% male and 40% female. The most common group of age founded was age 5-<10 years 39.4%, followed by 1-<3 years (25.8%), 3-<5 years (22.9%), 10 years 8.3%, and <1 year (3.6%). Fifty-four patients (49.5%) fulfilled 3 characteristics of atopy and there were 64 patients (58.7%) with positive SPT results. The sensitivity, specificity, positive predictive value and negative predictive value were 81.3%, 95.6%, 96.3%, and 78.2%, respectively. The 3 characteristics of atopy have good sensitivity and specificity to predict allergy in children.